Prevalence, patterns and reasons for ever use of tobacco among adult males in a rural field practice area of a tertiary healthcare institute of Haryana: a cross-sectional study - Annu Yadav; Seema Choudhary; Divyae Kansal; Ankesh Poonia; Nikhil Sheoran (International Journal Of Community Medicine And Public Health, 2026)
Background: Tobacco use continues to be a major public health challenge worldwide and remains highly prevalent in rural populations due to easy accessibility and misconceptions regarding its benefits. Therefore, this study estimates the prevalence, patterns, and reasons for ever use of tobacco among adult males residing in a rural field practice area of a tertiary healthcare institute of Haryana. Methods: A community based cross-sectional study was conducted in the catchment area of Primary Health Centre Agroha, Hisar, Haryana. A total of 350 adult males were selected through systematic random sampling. Data were collected using a predesigned and pretested interview schedule and analyzed using SPSS version 26.0. Results: Nearly two-thirds (63.1%) of the study population had experimented with tobacco at least once in their lifetime. Of these, 88.7% were regular users and hookah (46.2%) was the most commonly used smoking product. The majority (90.0%) of the participants reported initiating tobacco use between the ages of 15-25 years and multiple reasons (66.1%) were predominantly observed for initiation of tobacco use. Conclusions: Ever use of tobacco was highly prevalent among adult males in the study area, with most users being regular smokers. Early age tobacco initiation highlights the need for strengthened community-based preventive interventions, tobacco control, and cessation services in rural settings.